2007
DOI: 10.1111/j.1399-0004.2007.00897.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐Globin gene cluster polymorphisms are strongly associated with severity of HbE/β0‐thalassemia

Abstract: We evaluated the contribution of 67 single nucleotide polymorphisms (SNPs) within the beta-globin gene cluster to disease severity in groups of 207 mild- and 305 severe unrelated patients from Thailand with Hemoglobin E (HbE)/beta(0)-thalassemia and normal alpha-globin genes. Our analysis showed that these SNPs comprise two distinct linkage disequilibrium blocks, one containing the beta-globin gene and the other extending from the locus control region (LCR) to the delta gene, which are separated by a recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Three major HbF QTLs have been identified, which can modulate HbF levels and disease severity in SCD and b-thalassemia, 18,[26][27][28][29] namely, the BCL11A locus on chromosome 2p16, 16 the HMIP on chromosome 6q23, 20 and the b-globin locus. This study explores for the first time the frequency and association with HbF levels of genetic variants in these QTLs in SCD population from India.…”
Section: Discussionmentioning
confidence: 99%
“…Three major HbF QTLs have been identified, which can modulate HbF levels and disease severity in SCD and b-thalassemia, 18,[26][27][28][29] namely, the BCL11A locus on chromosome 2p16, 16 the HMIP on chromosome 6q23, 20 and the b-globin locus. This study explores for the first time the frequency and association with HbF levels of genetic variants in these QTLs in SCD population from India.…”
Section: Discussionmentioning
confidence: 99%
“…-thalassemia). Several mutations such as the b E -mutation at codon 26 or the mutation at IVSI-1 (G[T) are reported to be linked with the T allele of the XmnI polymorphism that is associated with a milder phenotype (Ma et al 2007;Winichagoon et al 2000). However, evidence regarding the most common b 0 -thalassemia mutation, codons 41/42 (-TCTT), showed that there was no effect to the results of this study, as an analysis conducted on a subset of patients with the same mutation also demonstrated similar results to those obtained from the analysis including all patients (Supplementary Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…2 Three major HbF quantitative trait loci (QTL) have been identified: the C/T single nucleotide polymorphism (SNP, rs7482144) at promoter nucleotide (nt) 158 bp 5Ј upstream of HBG2 on chromosome 11p15, 3 the HBS1L-MYB intergenic polymorphism (HMIP) on chromosome 6q23, 4 and the BCL11A polymorphism on chromosome 2p16. 5 They can modulate HbF and disease severity in ␤-thalassemia, [6][7][8][9] and sickle cell anemia. 10 The relative contributions of these 3 QTLs to HbF regulation appear to differ among populations.…”
Section: Introductionmentioning
confidence: 99%